Disturbing the dead ebook - Armstrong, Kelley (Rip Through Time, 2024)
Disturbing the Dead is the latest in a unique series with one foot in the 1860s and the other in the present day. The Rip Through Time crime novels are a genre-blending, atmospheric romp from New York Times bestselling author Kelley Armstrong. Victorian Scotland is becoming less strange to modern-day homicide detective Mallory Atkinson. Though inhabiting someone else's body will always be unsettling, even if her employers know that she's not actually housemaid Catriona Mitchell, ever since the night both of them were attacked in the same dark alley 150 years apart. Mallory likes her job as assistant to undertaker/medical examiner Dr. Duncan Gray, and is developing true friends—and feelings—in this century. So, understanding the Victorian fascination with death, Mallory isn't that surprised when she and her friends are invited to a mummy unwrapping at the home of Sir Alastair Christie. When their host is missing when it comes time to unwrap the mummy, Gray and Mallory are asked to step in. And upon closer inspection, it's not a mummy they've unwrapped, but a much more modern body.